Hak Pemeliharaan Ekonomi Anak dalam Keluarga Perspektif Peraturan Perundang-Undangan di Indonesia - Moh. Mundzir (LPPM Institut Agama Islam Al-Hikmah Tuban, 2020)
Abstrak, Too many laws and regulations in Indonesia that regulate the right to care for the child's economy which sometimes lead to legal disharmony between one regulation and another. This research is a doctrinal research with a synchronization pattern of law that is normative approach and qualitative descriptive analysis. The research aims to reveal whether or not the rule of law is synchronized in Indonesia relating to the economic rights of the child in the family, especially with The Convention on The Rights of The Child. The results of this study reveals that the material contained in several laws in Indonesia is in line, both between the The Convention on The Rights of The Child and other regulations such as the magnitude of the material for the economic right of child care, and some are not vertically and horizontally in line between legislation such as the boundaries of economic maintenance children and parents are allowed to take the child's property. Keyword, Regulations, Convention on The Rights of The Child, Children and Parents